Structural Equations: Analysis Of The Malcolm Baldrige Model (MBNQA) And Productivity In The Textile Sector Of Tungurahua (International Journal of Environmental Sciences, 2025)
The research analyzed the relationship between the dimensions of the Malcolm Baldrige National Quality Award (MBNQA) model and productivity in the textile sector of Tungurahua. A quantitative, non-experimental, and correlational approach was applied. A questionnaire was used, with questions structured around the seven criteria of the model and the elements of productivity. It was validated through an exploratory factor analysis KMO = 0.833; Bartlett p < 0.05 and with an acceptable Cronbach's alpha reliability = 0.848. Structural equations (SEM) were applied as a technique to identify latent relationships between the factors analyzed. The results obtained reflected a strong association between process management and productivity, while dimensions such as leadership and performance evaluation showed significant weaknesses. Around 50% of the companies surveyed reported that they do not apply formal quality tools or techniques for evaluating and monitoring business performance. The findings, while aligned with the application of the model and its contribution to improving organizational productivity, also reflect the need for leadership commitment, the adoption of efficient process management, and continuous evaluation and improvement.